Differential mechanism of ATP production occurs in response to succinylacetone in colon cancer cells - Lee, Phil Jun; Woo, Seung Je; Yoo, Hee Min; Cho, Namki; Kim, Hong Pyo (Molecules, 2019)
Our aim was to verify the potential ability of succinylacetone (SA) to inhibit mitochondrial function, thereby suppressing cancer cell proliferation. SA treatment caused apoptosis in HCT116 and HT29 cells, but not in SW480 cells, with mitochondria playing a key role. We checked for dysfunctional mitochondria after SA treatment. Mitochondria of HT29 cells were swollen, indicating damage, whereas in HCT116 cells, several mitochondria had a diminished size. Damaged mitochondria decreased ATP production and induced reactive oxygen species (ROS) in the cells. To understand SA-induced reduction in ATP production, we investigated the electron transfer chains (ETC) and pyruvate dehydrogenase kinase (PDK) activity, which prevents the transfer of acetyl- CoA to the TCA (tricarboxylic acid) cycle by inhibiting PDH (pyruvate dehydrogenase) activity. In each cell line, the inhibitory mechanism of ATP by SA was different. The activity of complex III consisting of the mitochondrial ETCs in HT29 cells was decreased. In contrast, PDH activity in HCT116 cells was reduced. Nicotinamide nucleotide transhydrogenase (NNT)-removing reactive oxygen species (ROS) was upregulated in HT29 cells, but not in HCT116 cells, indicating that in HT29 cells, a defense mechanism was activated against ROS. Collectively, our study showed a differential mechanism occurs in response to SA in colon cancer cells.
Keywords: Adenosine Triphosphate; Apoptosis; Cell Line, Tumor; Cell Proliferation; Cell Survival; Colonic Neoplasms; Enzyme Inhibitors; Heptanoates; Humans; Mitochondria; Reactive Oxygen Species; Apoptosis; ATP; Colon cancer cell lines; Oxidative phosphorylation; Pyruvate dehydrogenase; Succinylacetone